Comparison of a Self-Care Therapeutics Course Taught in the P1 vs the P2 Year. (April 2023) - Bald, Elizabeth M.; Kourtides, Demetrius; Cox, Nicholas; Raber, Hanna; Ruble, James H.; Richards, Boyd
Objective: The objective of this study was to compare student learning outcomes, behaviors, and attitudes in a non-prescription drug and self-care therapeutics course taught in the second professional (P2) year vs the first professional (P1) year at one pharmacy school.Methods: Mean performance of students by class year on case consultations and exam scores was compared. Focus groups with student volunteers and course teaching assistants (TAs) and one-on-one interviews with a subset of instructors were conducted by an outside educational evaluation specialist to capture perceptions of student learning behaviors and attitudes.Results: There was no difference in performance on graded case consultations (mean difference = 0.16, P = .74, 95% CI [−0.77 to 1.09]), mid-term examinations (mean difference = 0.53, P = .62, 95% CI [−1.59 to 2.65]), or final examinations (mean difference = 0.73, P = .57, 95% CI [−1.83 to 3.30]) between P1 and P2 students. P1 students reported being more consistent in completing pre-class readings and in feeling less distracted by other courses than did P2 students. Students, TAs, and instructors consistently spoke about advantages of the course in the P1 year (e.g., less stress and greater eagerness to learn and apply skills at work) and disadvantages in the P2 year (e.g., distraction from concurrent P2 integrated pharmacotherapeutics course and tension between real-world experience and constraints of grading rubric).Conclusion: P1 students, despite one year earlier in their curriculum, performed equally well as P2 students. All stakeholders agree that the advantages of teaching a self-care course on students' learning behaviors and attitudes in the P1 year outweigh disadvantages.